THE ORANGE TREE MOTIF AS PART OF THE “MYTH ABOUT ITALY” IN STENDHAL’S WRITINGS (Proceedings of Southern Federal University. Philology, 2012)
Belopolskaya E.V., Ponomaryova D.V.Keywords: the playwright Bulgakov, Don Quixote, Bakhtin, carnivalization, grotesque motif.Guided by Bakhtin’s position of particular vision of chivalry, the authorsof the article discover motives typical of romantic grotesque in thelittle-known third edition of M. Bulgakov’s “Don Quixote” (September 1938). The reduction of the resurgence moment of the hilarious turns out to be closely linked to the protagonist’s image. The authors’ observations throw light on the peculiar interpretation of the great story of the knight La Mancha by the 20th century playwright.